2004
DOI: 10.1158/0008-5472.can-3487-2
|View full text |Cite
|
Sign up to set email alerts
|

K-Ras and H-Ras Activation Promote Distinct Consequences on Endometrial Cell Survival

Abstract: A considerable amount of evidence indicates that Ras signaling contributes to the development of endometrial cancer. We previously demonstrated that endometrial cancer cells carrying oncogenic [12 Val]K-ras were susceptible to apoptosis. The present study examined the role of K-and H-Ras in the induction of apoptosis using rat endometrial cells (RENT4 cells). We found that constitutively activated K-Ras promoted apoptotic cell death, whereas the H-Ras mutant rescued rat endometrial cells from apoptosis. Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…[246][247][248][249][250][251] Mutations at the p85 subunit of PI3K have been detected in Hodgkin's lymphoma cells. 252 The p110 subunit of PI3K is frequently mutated (B25%) in breast and some other cancers but it not believed to be frequently mutated in leukemia.…”
Section: Roles Of the Pi3k/pten/akt/mtor Pathway In Leukemiamentioning
confidence: 99%
“…[246][247][248][249][250][251] Mutations at the p85 subunit of PI3K have been detected in Hodgkin's lymphoma cells. 252 The p110 subunit of PI3K is frequently mutated (B25%) in breast and some other cancers but it not believed to be frequently mutated in leukemia.…”
Section: Roles Of the Pi3k/pten/akt/mtor Pathway In Leukemiamentioning
confidence: 99%
“…Stably transfected cells were selected and isolated in growth medium containing 400 g/ml Zeocin (Invitrogen) to establish cell lines expressing KRas protein, previously described elsewhere. 35 Pooled populations were used for the assay. Cells were cultured with Dulbecco's modified Eagle's medium (DMEM) (Nissui, Seika, Japan) supplemented with 20 g/ml Gly-HisLys, 2 mmol/L glutamine, 80 IU insulin (Sigma-Aldrich, St. Louis, MO), and 10% fetal calf serum (FCS) (Hyclone, Logan, UT).…”
Section: Cell Culturementioning
confidence: 99%
“…Recent reports showed that K-ras mutation increases the sensitivity of human cancer cells to genotoxic stresses, such as 5-fluorouracil, tumor necrosis factor (TNF)-related apoptosis-inducing ligand, and irradiation (16)(17)(18). In addition, it was also reported that endometrial cancer cells carrying K-ras 12V are more sensitive to apoptosis (19). Recently, the Ras-NORE1-mammalian sterile20-like kinase 1 (MST1) complex has been reported to be involved in mediating Ras-induced apoptosis in NIH3T3 and HEK293 cells treated with tamoxifen (20).…”
Section: Introductionmentioning
confidence: 99%